From heparan glycobiology to stem cell therapy: a historical perspective - Victor Nurcombe (Academia Biology)
Glycobiology is one of the most diverse and exciting fields in biochemistry and has direct relevance to all biomedical disciplines, particularly for tissue development, homeostasis, and regulation, as well as for essential cell/cell communication and immunological processes. This overview discusses a number of milestones in the field from a historical perspective, which reflect the importance of glycobiological insights into tissue growth and repair. We discuss the importance of key experiments that revealed the important functions of heparan sugars in the extracellular matrix (ECM), such as the Gospodarowicz revolution for cell culture, the Edgar dose-response shift induced by ECM, and the Moscatelli migration experiment. The role of heparan sugars in sculpting developmental stem cell niches is extensively discussed. Furthermore, structure-function relationships are presented, which resulted in the recognition that specific sugar-moieties and sulfation states provide a “glycocode” that is analogous to the “genetic code” and the epigenetic “histone code”. Translational avenues include the selection and biochemical tuning of heparan sugars as nanoscale scaffolds that support cell signaling for specific applications in tissue engineering and regenerative medicine. If the important progress in the past 40 years is any guide, the field of glycobiology is about to enter a golden era, with realistic prospects for glycotherapies that encompass a range of clinical disorders.